Pengaruh Persepsi Manfaat, Persepsi Kemudahan, Fitur Layanan Dan Kepercayaan Terhadap Tingkat Kepuasan Pelanggan Linkaja Di Indonesia - Findy Meileny*; Tri Indra Wijaksana (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
The study was conducted to knows the impact of Perceived Usefulness, Perceived Ease of Use, Service Features, and Trust on LinkAja's Customer Satisfaction in Indonesia. Data collection in this study is done with questionnaires and data analysis is using quantitative analysis. This research uses purposive sampling kind of non-probability sampling technique and coonsist of 100 respondents. The analysis tools in this study used SPSS version 20. This research uses The Multiple Linear Regression Analysis Test and descriptive analysis. Result of this study describes that Perceived Usefulness (X1), Perceived Ease of Use (X2), Service Features (X3), Trust (X4), and Customer Satisfaction (Y) are in the poor category. While result of multiple linear regression in this study can be conducted the impact of Perceived Usefulness (X1), Perceived Ease of Use (X2), Service Features (X3), Trust (X4) has a positive and significant influence of LinkAja's Customer Satisfaction (Y) both partial and simultaneous.The other results obtained variables that influence LinkAja’s Customer Satisfaction in Indonesia is trust variable, it means the better the trust of the customer, the level of customer satisfaction will increase. Thus, companies must always strive to improve customer trust.